Before- and after-domain rotation of the free layer of an FeMn based spin valve - Lee, JH; Park, BK; Rhie, K; Choe, G; Shin, KH (ELSEVIER SCIENCE BV, 1999)
Magnetoresistance (MR) and Planar Hall effect (PHE) of Ta 50 Angstrom/NiFe 60 Angstrom/Co(90)Fe(10) 10 Angstrom/Cu 20 Angstrom/Co(90)Fe(10) 10 Angstrom/NiFe 23/Angstrom FeMn 100 Angstrom/Ta 50 Angstrom spin valve were measured with the magnetic field applied in the plane of the sample. A single batch thin film was etched parallel and perpendicular to the easy direction of the pinned layer. When the field and current were applied along the easy direction, we observed a clear evidence of before- and after-domain rotation of the free layer, near H = 0. Larger after-domain rotation of the free layer effect was observed in the sample etched along the hard axis, because the shape anisotropy tilted bias field made the hysteresis of the pinned layer have a longer tail beyond H > 0. (C) 1999 Published by Elsevier Science B.V. All rights reserved.
Keywords: ANISOTROPIC MAGNETORESISTANCE